Strategic IDPs Assessement - World Bank (World Bank, Washington, DC, 2016)
Integrated Development Plans (IDPs) have been introduced in Romania as a prerequisite for accessing EU funds under the Regional Operational Program (ROP). The IDPs designed for growth poles represent a specific category of strategic planning documents as: 1) they need to be considered within the frame of the national policy to whose implementation they contribute; and 2) they represent a first endeavor to think of development across functional areas rather than confined to the administrative borders of the main cities. The objectives of this report are: i) to carry out a strategic evaluation of the seven IDPs and assess how the current plans compare with the diagnostic of the challenges identified in the work on urban development; and ii) to provide clear recommendations for the improvement of existing IDPs which will contribute to the elaboration of the future generation of plans implemented during the next programming period and will help improve the targeting of investments to enhance their economic impact.